Repair of damaged composite materials after patching experimental investigation of influencing factors - Cetinkaya, Sukru; Pihtili, Hasim (Taylor & Francis Inc, 2025)
In this study, an experimental study was conducted on the reuse of composite materials after they were damaged. Since composite materials are difficult to recycle and reuse, their presence as waste in the environment is an ecological problem. Therefore, it is more convenient and economical to disassemble the damaged parts and make repairs instead of using new materials. In addition, due to the high cost of these materials, their repairs are preferred. For this study, after glass and carbon fiber-reinforced layer composite plates/sheets were produced, damage in the form of a 10 mm round hole was created. These damaged areas were made ready for repair by applying mechanical processes around them. For repair procedures, different adhesives and patches were applied under appropriate laboratory conditions, and the damaged samples were repaired. Various factors were taken into consideration during the repairs. These factors included the W/D ratio, adhesive thickness, adhesive type, fiber reinforcement angle change in the patch and base material (0, 15, 30, 45), patch thickness, and patch geometry. As a result, different destructive tests were applied to these repaired samples and thus the damage loads of each repair were determined. The results of these damage loads obtained for different factors were compared with the results of the current study in the literature and displayed in plots.
Keywords: Fiber-reinforced composite materials; repair; patch; adhesive/glued joints; damage load